2018
DOI: 10.1016/j.foodres.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of bentonite clay in cassava starch films for the reduction of water vapor permeability

Abstract: Complete factorial planning 2 was applied to identify the influence of the cassava starch(A), glycerol(B) and modified clay(C) content on the water vapor permeability(WVP) of the cassava starch films with the addition of bentonite clay as a filler, its surface was modified by ion exchange from cetyltrimethyl ammonium bromide. The films were characterized by X-ray diffraction(XRD), fourier transform by infrared radiation(FTIR), atomic force microscopy(AFM) and scanning electron microscopy(SEM). The factorial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 32 publications
2
16
0
4
Order By: Relevance
“…This decreasing effect of Mt on WVP of films has been observed in other studies (Romero-Bastida et al, 2015;Oliveira et al, 2016), and is ascribed to the so-called tortuous path effect, i.e. an increased diffusion path length for permeants such as water vapor through the matrix due to obstacles created by the presence of impervious particles (Tan and Thomas, 2017;Monteiro et al, 2018).…”
Section: Tensile Properties Wvp and Opacitysupporting
confidence: 75%
“…This decreasing effect of Mt on WVP of films has been observed in other studies (Romero-Bastida et al, 2015;Oliveira et al, 2016), and is ascribed to the so-called tortuous path effect, i.e. an increased diffusion path length for permeants such as water vapor through the matrix due to obstacles created by the presence of impervious particles (Tan and Thomas, 2017;Monteiro et al, 2018).…”
Section: Tensile Properties Wvp and Opacitysupporting
confidence: 75%
“…Similar results were reported by Lee et al who noted that the addition of 30 wt % halloysite to chitosan films resulted in a decrease of WVP by 14.18% [ 29 ]. A study by Monteriro et al indicated that the incorporation of bentonite into cassava starch resulted in a decrease of the WVP of the films [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Atomic Force Microscopy (AFM)In order to further understand the morphology of the starch films synthesized, a topographic study made by AFM to obtain qualitative (morphology) and quantitative (roughness) information of the different samples, based on the atomic interaction of their constituents[53]. Tri-and bidimensional topographic AFM images and bi-dimensional contrast phase images are presented in…”
mentioning
confidence: 99%